CURRICULUM DEVELOPMENT OF TEACHER EDUCATION INTEGRATED WITH ISLAMIC SCIENTIFIC TECHNOLOGY AND LOCAL WISDOM - Rustan, Edhy; Baderia, Baderia; Alauddin, Alauddin (Institut Agama Islam Negeri Palopo, 2019)
The aim of this research is to reveal the conditions of objectives and needs for curriculum development in the PGMI FTIK IAIN Palopo study program, develop a curriculum that is integrated with Islamic scientific technology and local wisdom, and provide the feasibility of the resulting curriculum model. This type of research is curriculum research and development with a mixed-methods approach. This research was carried out at PGMI FTIK IAIN Palopo. The subjects in this research are students, lecturers and the user community. The development process is carried out in 3 stages, namely (1) Preliminary study and Assessing Needs; (2) Reconstruction Phase; and (3) Curriculum implementation and monitoring stage. The results of the needs analysis show that integrating Islamic scientific technology and local wisdom is very necessary. The curriculum was developed by integrating Islamic scientific technology and local wisdom. The results of expert research show that it is valid and the results of testing the developed curriculum are also effective in use. Thus, an integrated Islamic scientific curriculum and local wisdom can be applied, especially in the PGMI FTIK IAIN Palopo.